Influence of elicitors on the enhancement of camptothecin accumulation and antioxidant potential in callus cultures of Chonemorpha fragrans - Ambujakshi, N. P.; Ravikiran, T.; Raveesha, H. R.
Chonemorpha fragrans (Moon)Alston is a valuable medicinal plant with various applications in pharmaceuticals for various diseases. The current study was designed to examine the role of elicitors on biomass, camptothecin production and the antioxidant capacity of callus culture. The different elicitors such as chitosan, salicylic acid, yeast extract, and glycine were employed in this study. The phytoconstituents were characterized and quantified by GC-MS and LC-MS analysis. Antioxidant capacity was assessed by DPPH, ABTS, reducing power, and phosphmolybdenum assay. Maximum biomass was achieved in 100 mg/L Gl elicited callus on Gamborg's medium augmented with 0.5 mg/L of 2, 4-D, and BAP. The higher antioxidant and secondary metabolites were higher in the Ct elicited callus. GC-MS analysis revealed the presence of phytoconstituents like ? - sitosterol, stigmasterol, and squalene. Higher Camptothecin (CPT)content was noticed in Ye supplemented callus. Therefore, our results are demonstrated that the elicitor supplements have the potential to enhance biomass and phytoconstituents in leaf-derived callus cultures of C. fragrans.
Keywords: CHITOSAN; GC-MS; LC-MS/MS; SALICYLIC ACID; YEAST EXTRACT